Analysing the structuring of knowledge in learning networks - Carvalho, Lucila; Goodyear, Peter (Proceedings of the International Conference on Networked Learning, 2014)
Knowledge plays a significant role in networked learning. Epistemic activities, and the structures that support such activities, do not just spring into life when a networked learning resource is created. They exist prior to, and outside of, any specific networked resource. They go on in the world. So epistemic actvities and structures can be seen as part of a broader socio-cultural context. In this paper, we argue that people who design for networked learning benefit from having a richer repertoire of ways of undertsanding relationships between epistemic activities and the structures that support them, and of viewing these in their social contexts. Educational designers need to be aware there are different ways of expressing knowledge, associated with implicit values that underlie knowlegde practices within any social context. These varied ways of expressing knowledge have diverse effects on learners' activities. Understanding such connections is useful when designing new networked learning resources, or when devising ways to improve exisiting learning networks. Using an approach from the sociology of knowledge, this paper explores the structuring of knowledge in a case study of networked learning drawn from an undergraduate design course about graphics and programming. The course uses a computer-based platform called Peep to extend what would otherwise be a set of timetabled, lab-based learning and teaching activities. Students and teachers can interact using Peep, at any time, from any location. These networked learning activities involve a mixture of lecturer-led tasks and student driven collaborations, including requests for and offers of help, and sharing and discussing code and graphical designs. Our focus in this case study is on variations in the degree to which the knowledge being dealt with is dependent on its context for meaning and condensed. Our analysis reveals that one of the design elements of Peep - the code editor - facilitates a distinctive, important epistemic activity. The code editor enables the "object of discussion" (programming and the visual and animated effects of it) to come to the fore. Instead of students having to describe phenomena, events or processes that happen elsewhere, they each have the object of their discussion in front of them, embedded within all of Peep's spaces for learning. Our analysis explores the relations between this design feature and Peep's support for students' discussions of complex concepts, sharing and exchanging views, and building on each other's ideas and work.